Pengaruh Kompensasi, Disiplin Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan - Arditi Nila Handayani; Asih Handayani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to examine the significance of the influence of compensation, work discipline and job satisfaction on employee performance (case study on PT Rumpun Sari Kemuning, Ngargoyoso District, Karanganyar Regency). This form of research is a survey. The population in this research is 300 employees. The sample in this research was 75 labor employees obtained from the Slovin Formula. The sample sampling method uses random sampling techniques. This research uses a descriptive data analysis method, and is analyzed using multiple linear regression analysis. The data collection strategy uses questionnaires. The findings show that compensation, work discipline and job satisfaction have a significant effect on the performance of PT Rumpun Sari Kemuning employees.